2016
DOI: 10.3171/2016.4.spine16157
|View full text |Cite
|
Sign up to set email alerts
|

Lateral interbody fusion combined with open posterior surgery for adult spinal deformity

Abstract: OBJECTIVE Lateral interbody fusion (LIF) with percutaneous screw fixation can treat adult spinal deformity (ASD) in the coronal plane, but sagittal correction is limited. The authors combined LIF with open posterior (OP) surgery using facet osteotomies and a rod-cantilever technique to enhance lumbar lordosis (LL). It is unclear how this hybrid strategy compares to OP surgery alone. The goal of this study was to evaluate the combination of LIF and OP surgery (LIF+OP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Interestingly, in this study, the authors found better clinical outcomes, less EBL, fewer complications, and faster recovery in the hybrid group (LLIF and open posterior surgery) compared to the group with open posterior surgery alone [37].…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, in this study, the authors found better clinical outcomes, less EBL, fewer complications, and faster recovery in the hybrid group (LLIF and open posterior surgery) compared to the group with open posterior surgery alone [37].…”
Section: Discussionmentioning
confidence: 55%
“…Anterior column release (ACR) is a powerful surgical technique for achieving spinopelvic balance in adult patients with sagittal plane deformities (Park et al, ; Turner et al, ; Demirkiran et al, ; Hamilton et al, ; Saigal et al, ; Strom et al, ; Than et al, ; Mundis et al, ; Theologis et al, ). ACR is performed through a lateral approach or through an anterior approach with intervertebral diskectomy and release of the anterior longitudinal ligament (ALL), followed by placement of a hyperlordotic interbody device.…”
Section: Introductionmentioning
confidence: 99%
“…A second‐stage posterior approach is typically performed to further stabilize the construct; posterior column osteotomies are often utilized during the posterior approach to maximize correction. The posterior approach has been described using both open and minimally invasive techniques (Park et al, ; Turner et al, ; Strom et al, ; Than et al, ; Mundis et al, ). Numerous studies have demonstrated that ACR can produce comparable lordotic correction as posterior‐only three‐column osteotomies (3CO), with similar complication profiles and less blood loss (Park et al, ; Turner et al, ; Demirkiran et al, ; Hamilton et al, ; Saigal et al, ; Strom et al, ; Than et al, ; Mundis et al, ; Theologis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Correction of kyphosis at disc level -such as through multilevel posterior interbody fusion (PLIF) 1) , dorsal ventral dorsal correction 2) , and lateral lumbar interbody fusion 3) is indicated for cases in which several intact discs remain. However, for revision cases, the number of intact discs that can be used for kyphosis correction is limited, and pedicle subtraction osteotomy (PSO) that can correct kyphosis at the vertebral body is indicated in most cases.…”
Section: Introductionmentioning
confidence: 99%